Emerging PPARγ-Independent Role of PPARγ Ligands in Lung Diseases - Kulkarni, Ajit A. (Hindawi Publishing Corporation, 2012)
Peroxisome proliferator activated receptor (PPAR)-γ is a nuclear hormone receptor that is activated by multiple agonists including thiazolidinediones, prostaglandins, and synthetic oleanolic acids. Many PPARγ ligands are under investigation as potential therapies for human diseases. These ligands modulate multiple cellular pathways via both PPARγ-dependent and PPARγ-independent mechanisms. Here, we review the role of PPARγ and PPARγ ligands in lung disease, with emphasis on PPARγ-independent effects. PPARγ ligands show great promise in moderating lung inflammation, as antiproliferative agents in combination to enhance standard chemotherapy in lung cancer and as treatments for pulmonary fibrosis, a progressive fatal disease with no effective therapy. Some of these effects occur when PPARγ is pharmaceutically antagonized or genetically PPARγ and are thus independent of classical PPARγ-dependent transcriptional control. Many PPARγ ligands demonstrate direct binding to transcription factors and other proteins, altering their function and contributing to PPARγ-independent inhibition of disease phenotypes. These PPARγ-independent mechanisms are of significant interest because they suggest new therapeutic uses for currently approved drugs and because they can be used as probes to identify novel proteins and pathways involved in the pathogenesis or treatment of disease, which can then be targeted for further investigation and drug development.